2023
DOI: 10.1088/1742-6596/2505/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

A non-symmetric Gaussian wake model for lateral wake-to-wake interactions

Abstract: In this paper, we propose a new non-symmetric Gaussian wake model, which allows for different lateral expansions on the two sides of a wake to account for its interaction with neighbouring wakes. The proposed model is formulated following classical speed-deficit assumptions and momentum conservation. Departing from the existing literature, a non-symmetric Gaussian function is used to represent the velocity deficit in the wake. Accordingly, different wake expansions are assumed on the two sides of the wake, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In various environmental conditions, they indicated that yaw effects can induce significant load variation, which is detrimental to structural stability. In another aspect of the research, Vad et al [33] proposed a new model of a non-symmetric Gaussian wake, where the wake affecting the actuator disk of a leading turbine does not exhibit uniformity, thus leading to partial wake overlap. This model uses a non-symmetric Gaussian function to represent the velocity deficit in the wake, resulting in different forms of wake expansion and, consequently, the formation of a partial wake.…”
Section: Introductionmentioning
confidence: 99%
“…In various environmental conditions, they indicated that yaw effects can induce significant load variation, which is detrimental to structural stability. In another aspect of the research, Vad et al [33] proposed a new model of a non-symmetric Gaussian wake, where the wake affecting the actuator disk of a leading turbine does not exhibit uniformity, thus leading to partial wake overlap. This model uses a non-symmetric Gaussian function to represent the velocity deficit in the wake, resulting in different forms of wake expansion and, consequently, the formation of a partial wake.…”
Section: Introductionmentioning
confidence: 99%